Livelihood Sustainability and Coupling Coordination of Farming Households with Different Grazing Intensities in Loess Hilly Region - Wang Peng; Ma Shengli; Xu Mingxiang (Shuitu baochi tongbao)
[Objective] The structure and sustainability of livelihood factors and their coupling coordination under different grazing intensities were studied in order to provide a scientific basis for optimizing the livelihood strategies of farming households, increasing their economic income, and realizing rural revitalization. [Methods] Taking the typical district of loess hilly area as an example, based on the sustainable livelihood framework, constructing the evaluation index system from multiple livelihood elements, combining the survey data of farmers and mathematical modeling, a comprehensive study was conducted on the sustainability of livelihoods of farmers with different grazing intensities and their coupled and coordinated development. [Results] ① Grazing intensity enhanced the sustainability of farmers’ livelihood capital, but there were significant differences in the effects on the sustainability of livelihood environment, livelihood strategies, and livelihood outcomes. ② Livelihood sustainability was highest under moderate grazing intensity, and livelihood capital, livelihood environment, livelihood strategy, and livelihood outcome sustainability increased by 37.86%, 3.83%, 9.92% and 30.45%, respectively, compared with non-grazing farmers. ③ The coupling coordination development characteristics followed the order of moderately grazing farmers > lightly grazing farmers > heavily grazing farmers > non-grazing farmers. Farmers’ livelihood coupling degree was higher than the coordination degree, indicating that the livelihood system of grazing farmers in the loess hilly region had a strong inter-role intensity, and that good coupling and synergistic development within the system had not yet formed. Therefore, it will still be necessary to further strengthen the transformation and upgrading of farmers’ livelihoods to improve their livelihood sustainability in the future. [Conclusion] Moderate grazing can increase livelihood capital and optimize livelihood strategy for farming households in the loess hilly region, and increase the livelihood sustainability and economic income of farming households.